Relationship between measures of aerobic fitness, speed and repeated sprint ability in full and part time youth soccer players - Gibson, N.; Currie, J.; Johnston, R.; Hill J. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of the study was to investigate the relationship between repeated sprint ability (RSA) involving changes in direction, short linear sprinting and aerobic capacity in young elite soccer players. A secondary aim was to assess any differences in performance of these assessments between players of different age groups. Methods: Thirty-two male adolescent soccer players belonging to the same elite club academy were assessed for RSA comprising 6 x 40m efforts interspersed by 25s recovery, linear sprinting speed over 15m, and aerobic capacity via the YYIE2 assessment. Results: There was a significant correlation between performance in the YYIE2 and RSA total time, RSA fastest sprint and RSA percentage decrement (r = -0.71, -0.53, and -0.52 respectively. PConclusion: Assessments of RSA over 40m and incorporating changes of direction appear to be significantly correlated with YYIE2 performance in young elite level soccer players. In addition older players performed significantly better in the YYIE2 assessment and RSA protocol but not in short linear sprinting. These results have implications for the design of assessment protocols for young elite soccer players of different ages.